Probiotics, prebiotics, and symbiotics in the irritable bowel syndrome - Guzmán Calderón, Edson (2012)
Irritable intestine syndrome is a common condition that affects millions of persons all over the world. It has a significant impact in the quality of life of affected persons, influencing their social and working environments and leading to individual suffering and a macroeconomic impact because of increased absenteeism and poor working performance. Prebiotics and probiotics are supplements of nondigestible diet, made up of some chemicals and live microorganisms (bacteria or yeasts from the intestinal commensal flora), which, when ingested in optimal amounts (symbiotic therapy), are beneficial for human health. With no doubt, the intestinal mucosa is the greatest surface in the human body exposed to external stimuli, and it also contains a high proportion of immune cells. Any alteration in homeostasis between beneficial and potentially harmful microorganisms in the intestinal microflora is expressed as an increased risk for the occurrence of infectious and immune and inflammatory diseases; therefore, prebiotics and probiotics may help to maintain a harmonic environment in the intestine.